PLASMA AND ERYTHROCYTE CHOLINESTERASE ACTIVITIES IN CHILDREN FROM YUCATAN, MEXICO: RELATIONSHIP WITH ANTHROPOMETRY AND OBESITY - Rodriguez-fuentes, Gabriela; Arcega-cabrera, Flor; Fargher, Lane F (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To examine cholinesterase activities in children from three towns in Yucatan, Mexico and their relationship with anthropometry. Methods: Plasma and erythrocyte cholinesterase a ctivities were measured in 104 children from Ticul, Merida and Progreso. Differences between gender, sampling sites and body mass index (BMI ) groupÂ  were evaluated. Weight, height, BMI, hip and waist circumferences were correlated with cholinesterase activities. Results: Significant differences in the waist circumference and BChE activity were found among sites. Children from Ticul presented higher BChE activity compared to children from the other towns. Children from Progreso had a smaller hip circumference compared to children from the other two locations. There was a high prevalence of overweight and obese children (40.3%). The results indicated that obese children had higher BChE activity respect to healthy weight children. As expected, there were also significant waist and hip circumference differences for BMI groups. The results demonstrated a positive significant correlation between BChE activity and weight, waist and hip circumference. Conclusions: These results support the hypothesized role of BChE in lipid metabolism. Because of the high prevalence of obese children in Mexico, BChE activity may be used as a biomarker in combination with anthropometry to monitor obesity. Keywords: Cholinesterase, Children, Anthropometry, Obesity.